Moral Character, Reformed Theology, and Jonathan Edwards. (August 2017) - Crisp, Oliver D.
Reformed theology is often thought to be antipathetic to virtue theory. However, Jonathan Edwards is a counterexample to this way of thinking. In this article, I offer an account of Edwards's moral thought as a case study of Reformed theology that is also a species of virtue theory, focusing on what he says about the formation of character. I argue that key doctrinal commitments drive his moral theology, and generate some interesting problems for his ethics. Although his work is not without shortcomings, Edwards is a thinker whose moral theology might be usefully repaired and retrieved by contemporary theologians in the Reformed tradition for whom 'duties are founded on doctrines'.